Adsorption behaviour of carboxylic acid in cooking oil waste on steel in aqueous solution / Junaidah Jai, Wan Shabuddin Wan Ali and M.H. Ekramul - Jai, Junaidah; Wan Ali, Wan Shabuddin; Ekramul, M.H. (Research Management Institute (RMI), 2013)
Mild steel is commonly used as constructional material in many industries due to its excellent mechanical properties and low cost. However, mild steel is easily corroded when exposed to a corrosive environment. Palm cooking oil waste (PCOW) was introduced as a new organic corrosion inhibitor due to its fatty acids content. The objective of this study is to investigate the corrosion inhibition behaviour of PCOW inhibitor (PCOWI) against corrosion. The corrosion inhibition and inhibitor adsorption processes of PCOWI on mild steel in 1 M HCI were investigated at 299, 323 and 343K by using weight loss test and potentiodynamic polarization test. The weight loss test had shown that the inhibition efficiency (IE) increased with increasing concentration of PCOWI at all temperatures under study. However, the IE decreased with increasing of temperature. The maximum inhibition efficiency 100% was observed in the presence of 0.25 M inhibitor at 299K. Potentiodynamic polarization studies revealed that PCOWI behaves as a mixed type inhibitor. The experimental data fitted into Temkin adsorption isotherms. PCOWI exhibits a very good performance as a corrosion inhibitor for mild steel in 1M HCI.